A solution of the fractional differential equations in the setting of b-metric space - Afshari, H.; Karapinar, E. (Carpathian Mathematical Publications, 2021)
In this paper, we study the existence of solutions for the following differential equations by using a fixed point theorems \[ cases D^μ_cw()± D^ u_cw()=h(,w()),& J, 0< u<μ<1, w(0)=w_0,& cases \] where D^μ, D^ u is the Caputo derivative of order μ, u, respectively and h:J× R→ R is continuous. The results are well demonstrated with the aid of exciting examples.